2007
DOI: 10.1002/app.26690
|View full text |Cite
|
Sign up to set email alerts
|

Recycled PET nanocomposites improved by silanization of organoclays

Abstract: Recycled PET/organo-modified montmorillonite nanocomposites were prepared via melt compounding as a promising possibility of the used beverage bottles recovery. According to our previous work, the three suitable commercial organoclays Cloisite 25A, 10A, and 30B were additionally modified with [3-(glycidyloxy)propyl]trimethoxysilane, hexadecyltrimethoxysilane and (3-aminopropyl)trimethoxysilane. The selected organoclays were compounded in the concentration 5 wt % and their degree of intercalation/delamination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Finding proper methods of recycling poses a new challenge from the ecological and economic points of view. In particular, only a few studies on recycled PET recovery for the purpose of nanocomposite materials with improved processing and utility properties are found in the literature . Generally, three preparation methods are used for polymer nanocomposites: in situ polymerization, solution mixing, and melt mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding proper methods of recycling poses a new challenge from the ecological and economic points of view. In particular, only a few studies on recycled PET recovery for the purpose of nanocomposite materials with improved processing and utility properties are found in the literature . Generally, three preparation methods are used for polymer nanocomposites: in situ polymerization, solution mixing, and melt mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, only a few studies on recycled PET recovery for the purpose of nanocomposite materials with improved processing and utility properties are found in the literature. [14][15][16][17] Generally, three preparation methods are used for polymer nanocomposites: in situ polymerization, solution mixing, and melt mixing. Among the three, melt compounding is the preferred method for the preparation of polymer nanocomposites because of its environmental and economic advantages such as the absence of solvents and monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would decrease the desired properties of organoclay compatibilized blends. 11 This article reports the preparation of a new thermally stable organosilicate, for compatibilization of immiscible PET/PE blends. Phosphonium 8,[15][16][17] or immidazolium-based surfactants 10,18-23 would be worth being considered for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…In the particular case of polymer matrix/organoclay systems, many authors have reported the effect of thermal stability of the clay organomodifier on the dispersion of the organoclay nanoplatelets in the matrix and the resulting mechanical properties. [6][7][8][9][10][11] To our knowledge, no study has addressed the effect of surfactant thermal degradation on the morphology and induced mechanical properties of immiscible polymer blends yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation